STUDY ON PRE-INDEPENDENCE AND INDIAN WRITERS’ - Randheer Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
Poetry held a significant role in the canon of literary works. In the composition of poetry, vivid style and subject matter became more common. On the literary stage of the globe, the poem or poetries written in English hold a prestigious place. The history of English poetry and prose may be traced all the way back to the 7th century and continues on far into the decades that followed the Norman invasion in 1066. A time period that is frequently referred to as Anglo-Saxon England. The caedman’s hymn from the seventh century is the earliest poetry that has been found. The greatest defining characteristic of old English poetry was the use of an alliterative poetic pattern. The emphasis is placed throughout an alliterative phrase on the initial consonant sound that is emphasised. A line. Several different schools of thought, including as the alliteration and assonance, carswrametaphor, and variety schools. The use of litotes became common in poetic writing. The vast majority of old English poetry were not documented with authars, therefore very few of their authors’ names have survived. The glorification of the warrior, the adventurer, and the conqueror was one of the most prominent features of old English poetry. There are two distinct forms of poetry written in old English. 1) The Heroic Pre-Christian Germanic Culture, and 2) the Christian Culture. Only a handful of poets from the Anglo-Saxon period are known to have existed. Theywerebede, Caedmon Alfred and Cynewulf.